(untitled) (Yangi O’zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2024)
This studies article goals to delve into the intricacies of brain meningioma, a neurological situation characterized by using the abnormal growth of neoplasms inside the meninges. By undertaking an in-depth evaluation, we are seeking to explore the etiology, pathomorphology, diagnostic techniques, remedy options, and advancements in coping with this situation. This observe now not best ambitions to beautify knowledge however also make contributions to the ever-evolving discipline of neurology.